2012
DOI: 10.1016/j.jaerosci.2012.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Experimental determination of deposition of diesel exhaust particles in the human respiratory tract

Abstract: a b s t r a c tDiesel emissions are a major contributor to combustion-generated airborne ambient particles. To understand the role of diesel particulate emissions on health effects, it is important to predict the actual particulate dose deposited in the human respiratory tract, with respect to number, surface area and mass. This is complicated by the agglomerate nature of some of these particles. In this study the respiratory tract deposition fraction in the size range 10-500 nm, was determined for 10 healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
109
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 128 publications
(116 citation statements)
references
References 58 publications
4
109
0
3
Order By: Relevance
“…The set-up used for the respiratory tract deposition measurements was an improved version of a set-up described in several previous publications (e.g., Löndahl et al, 2006;Rissler et al, 2012), and followed the general experimental guidelines described in Löndahl et al (2014). The new setup is referred to as RESPI 2 .…”
Section: The Respi 2 Set-upmentioning
confidence: 99%
See 2 more Smart Citations
“…The set-up used for the respiratory tract deposition measurements was an improved version of a set-up described in several previous publications (e.g., Löndahl et al, 2006;Rissler et al, 2012), and followed the general experimental guidelines described in Löndahl et al (2014). The new setup is referred to as RESPI 2 .…”
Section: The Respi 2 Set-upmentioning
confidence: 99%
“…An SMPS classifies the particles according to their mobility diameter, d me (identical to the thermodynamic diameter). The mobility diameter is related to the diffusivity of the particles and has been proven to be the equivalent diameter that best describes the lung deposition for particles < 300 nm), regardless of particle shape or density (Heyder et al, 1986;Schmid et al, 2008;Rissler et al, 2012). Deposition by diffusion is governed by the particle diffusivity, D, which is related to mobility diameter as 1/d me .…”
Section: The Respi 2 Set-upmentioning
confidence: 99%
See 1 more Smart Citation
“…The estimations of volume and surface area are based on the assumption of spherical particles. Since freshly emitted soot particles, in several studies, have been shown to be highly agglomerated and thus far from spherical (Park et al, 2003;Rissler et al, 2012) such assumption could result in a severe overestimation of the deposited particulate volume and an underestimation of surface area when calculated from mobility number size distributions (as measured by a mobility particle sizer type of particle number size distribution instrument) . However, in the case of the particles found in Lycksele during the campaign there are several factors that indicates that the assumption of spherical particles is the best assumption to be made.…”
Section: Respiratory Tract Deposition For the Surface Area And Volumementioning
confidence: 99%
“…1 Potential exposure risk in manufactured nanoparticle (MNP) process through a typical life cycle adapted from Thomas et al (2009) An important source of PM 2.5 is from diesel exhaust, which is a complex mixture of hundreds of constituents in either gas or particle form (Wichmann 2007). The diesel exhaust typically mainly consist of carbon and absorbed organic compounds and other metals and trace elements, thus they are highly respirable and have a large surface area (Risslera et al 2012). The diesel exhaust particles entering the respiratory tract would be a risk factor for the development of diseases of the respiratory system (Yoshizaki et al 2015).…”
Section: Nanoparticle Pollution Impact On Human Health In China Nanopmentioning
confidence: 99%